Atmospheric corrosion of hot dip galvanized structural steel exposed to the tropical climate of Thailand - BUNPHOT, Adithep; SANCHAROEN, Pakawat; TANGTERMSIRIKUL, Somnuk; CHAISOMPHOB, Taweep (Journal of Metals, Materials and Minerals, 2025)
Hot dip galvanized steels were tested in the atmospheric tropical climate environments of Thailand for 12 month from March 2021 to March 2022. Three locations were studied, i.e. a rural area at Saraburi in the central part, an industrial area at Chonburi in the eastern part, and a coastal/urban area at Songkhla in the southern part of Thailand. The thickness loss of the galvanized steel samples was measured by the weight loss method. Types of corrosion products observed on the samples were zincite, wulfingite, hydrozincite, and simonkolleite. All of them were found on the sample at Songkhla. Three of them, except simonkolleite, were found on the sample at Chonburi. Only two of them, zincite and wulfingite were found on the sample at Saraburi. In addition, pit corrosion was found to be severe on the sample at Songkhla in the shape of a meteor crater.